Pressure injury prevalence and risk factors in Chinese adult intensive care units: A multi‐centre prospective point prevalence study. Issue 3 (5th July 2021) - Lin, Frances Fengzhi; Liu, Yu; Wu, Zijing; Li, Jing; Ding, Yanming; Li, Chunyan; Jiang, Zhixia; Yang, Jing; Wang, Kefang; Gao, Jie; Li, Xiaohan; Xia, Xinhua; et al.
Abstract: Despite increasing preventive efforts, pressure injury still occurs in intensive care patients. This study was aimed to describe pressure injury prevalence, risk factors, and prevention practices in adult intensive care patients. This was a multi‐centre, one‐day, prospective point prevalence study in which a total of 198 intensive care units from 21 provinces in China participated. Overall and ICU‐acquired prevalence in intensive care patients were 12.26% and 4.31%, respectively. Consistent with earlier reports, almost half of the ICU‐acquired pressure injuries were at stage I, one‐fourth were at stage 2, and the most common body sites for pressure injuries were sacral and heel region. Risk factors identified were consistent with prior studies. Repositioning was the most commonly used pressure injury prevention strategy, followed by alternating pressure mattresses/overlays, floating heels, and air‐filled mattresses/overlays. These reflect a good level of adherence to recommended international pressure injury prevention clinical practice guidelines. The results provide a baseline reference for overall and ICU‐acquired prevalence among adult intensive care patients in China. Future research on what contributed to the lower pressure injury incidence in China needs to be conducted to inform healthcare organisations on their future preventive strategies for pressure injury prevention.